Formulation and Physical Evaluation of Liquid Shampoo Combining Patchouli Leaf Extract and Coconut Oil as an Antidandruff Shampoo - Wahyuni, Risma Sri; Hasriyani, Hasriyani; Arif, Fahrudin (Advances in Healthcare Research, 2025)
Purpose: Dandruff is a scalp condition that affects approximately 50% of the global population and 26% of the population in Indonesia. This study aims to formulate and evaluate various formulations of liquid shampoo containing a combination of patchouli leaf extract (Pogostemon cablin Benth.) and coconut oil as an alternative natural-based anti-dandruff shampoo. Research Method: This study used a quantitative approach with an experimental design. The formulation consisted of a combination of patchouli leaf extract at concentrations of 0.5%, 0.75%, and 1% and coconut oil at concentrations of 2%, 3%, and 4%. Quality evaluation was conducted through organoleptic testing, homogeneity testing, pH measurement, foam height measurement, viscosity measurement, and skin irritation testing on 15 respondents. Results and Discussion: All formulas (F0, F1, F2, F3) meet the physical quality criteria for shampoo. Organoleptic testing indicates that the formula has a thick liquid consistency, is homogeneous, and ranges in color from clear to dark green, with a green tea aroma. The average pH is within the safe range (6.75–5.31). Foam height and viscosity are within normal limits, and no respondents reported any irritation complaints. Implications: The formulation of liquid shampoo combining patchouli leaves and coconut oil can be a potential solution in the development of safe, natural-based anti-dandruff products. This study provides scientific contributions to the herbal cosmetics industry in Indonesia.